Memahami Tipologi Pesantren dan Madrasah sebagai Lembaga Pendidikan Islam Indonesia - Muhammad Rouf (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2016)
AbstractIslamic Boarding School are the two kinds of Islamic educational institutions, in addition to other educational institutions. The development of Islamic Boarding schools have a long span of history in Indonesia is an original model of education in Indonesia and also in collaboration with Western modern education. Typology include boarding schools Salaf, khalaf and mix each tiered start primary, junior, intermediate and advanced high level. While the madrasah is a formal educational institution distinctively Islamic covering Raudhatul RA (RA), Government Elementary School (MI), Madratsah Tsanawiyah (MTs), Madrasah Aliyah (MA) and Madrasah Aliyah Vocational (MAK). Islamic schools can be a mainstay and international standing by means keeping good old traditions and take the new methods are better in improving the quality of education.